Sensitivity and specificity of sentinel lymph node biopsy in patients with oral squamous cell carcinomas using indocyanine green fluorescence imaging. Issue 8 (August 2018) - Al-Dam, Ahmed; Precht, Clarissa; Barbe, Armelle; Kohlmeier, Carsten; Hanken, Henning; Wikner, Johannes; Schön, Gerhard; Heiland, Max; Assaf, Alexandre T.
Abstract: Purpose: The purpose of this clinical study was to evaluate the sensitivity and specificity of cervical sentinel lymph node biopsy after mapping with indocyanine green fluorescence (ICG) for imaging early-stage oral cancer. Patients and methods: A sentinel lymph node biopsy (SLNB) was performed during a selective neck dissection (SND) in 20 patients with oral squamous cell carcinoma (OSCC, cT1 or cT2, N0 status). The sentinel lymph nodes (SLN) were identified using an infrared video camera after ICG injection. Lymph nodes were examined histologically. The endpoint of this study was to investigate the rate of false-negative results in SLNB. Results: Sentinel lymph nodes could be detected after 8.1 min (range 1–22 min). In eight out of 20 cases, lymph node metastases were found during histopathological evaluation of the neck dissection specimen. In four cases a metastasis could be found in the detected SLN (sensitivity 50%). In the other four cases metastases were found in different lymph nodes. Specificity was 100%, positive predictive value 100%, and negative predictive value 75%. Conclusion: In this study, reliability of sentinel lymph node biopsy after ICG imaging could not be verified, as there were false-negative results in 50% of the cases. Therefore, SND can still be recommended as for patients with cT1 or cT2 OSCC, and a N0 neck status.